Iskandar Malaysia: an analysis of regional planning and development - Rabe, Noor Suzilawati (IIUM Press, 2017)
This book entitled “Iskandar Malaysia: an analysis of regional planning and development” describes the formation of Iskandar Malaysia from author’s perspective and critical review of various literatures on regional development. In the recent years, striving towards achieving economic prosperous and with the fast and furious plan-making has resulted a vital role of regional planning and development in Malaysia. Hence, a deep insight into how planning and development of region is changing would hopefully be a usefully references for all reader in understanding the process and its relation towards current regional development. Iskandar Malaysia development region was established in 2006 with the introduction of a new single authority known as the Iskandar Regional Development Authority (IRDA). This authority is governed by the statutory IRDA Act of 2007 with a new proposed master plan named Comprehensive Development Plan and Iskandar Malaysia development blueprints for the region.